Juridical Review of the Legal Strength of Collective Agreements as a Result of Mediation in Dispute Resolution of Termination of Employment - Yolanda Adelia (Universitas Negeri Semarang, 2025)
Industrial relations disputes, particularly those related to termination of employment, are a significant issue in the labor sector that require fair and just legal resolution. One of the dispute resolution methods regulated under Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes is mediation. The results of the mediation process are formalized in a joint agreement which can be registered at the Industrial Relations Court to obtain executorial legal force. However, in practice, violations of the contents of the joint agreement are still frequently found, even after the agreement has been ratified by the court. The joint agreement resulting from mediation and registered at the Industrial Relations Court (PHI) has binding legal force and can be executed like a court ruling. Nevertheless, violations of its implementation are still encountered, especially in cases of employment termination. This article analyzes the legal consequences of non-compliance with the joint agreement as well as the available execution mechanisms. The study results show that disregarding a valid and registered joint agreement may incur legal sanctions and affect the overall effectiveness of the industrial relations dispute resolution system. Strict law enforcement, institutional strengthening, and increased legal literacy are required as strategic steps to enhance legal protection for workers.